Energy analysis for food industries in Malaysia / Mohamed Bashir Ali Bashir - Ali Bashir, Mohamed Bashir (2012)
The industrial sector is the largest consumer of energy in Malaysia. Malaysian food industries consume a significant amount of energy, about 14% of total manufacturing energy consumption. Therefore, the recent increase in energy cost has created has an essential consequence for developing alternative energy efficient technologies. In this case, energy efficiency means reduction of environmental degradation, increase of sustainability and cost savings. This dissertation focuses on the energy savings, economic benefits and emission reductions. These objective could be achieved by installation of variable speed drives, high efficiency motors, waste heat recovery unit of the boiler, new efficiency lamp (T5) for lighting and repairing, purpose of critical equipment in Malaysian food industries. It has been estimated that the total amount of 1,428, 2,129 and 2,466 MWh energy savings can be achieved annually by utilizing high efficiency motors for 50%, 75% and 100% motor loads respectively. It was also found that for different motor loads, an estimated US$91,385, US$136,252 and US$157,832 could be saved in anticipated energy costs and subsequently 843, 1,257 and 1,456 tons of CO2 emission reductions could be obtained at 50%, 75% and 100% motor loads respectively. It was also found that, the average of payback period associated with energy savings are about 2.01, 1.61 and 1.40 years for 50%, 75% and 100% motor loads respectively. Similarly, sizeable amount of energy can be saved using VSDs, waste heat recovery, new efficiency lamps (T5) and repairing leakages, resulting to curb energy costs. Furthermore, a considerable reduction in the amount of emissions can be obtained together with the associated energy savings for different energy savings strategies. In addition, the payback period for different energy savings strategies has been firmly established.